Discovery of SIRT7 Inhibitor as New Therapeutic Options Against Liver Cancer - Zhang, Chen; Li, Yaqi; Liu, Bohao; Ning, Chao; Li, Yimin; Wang, Ying; Li, Zhuan (Frontiers in Cell and Developmental Biology, 2022)
Optimal therapeutic strategies for liver cancer patients are remain challenging due to the high recurrence rates after surgical resection and chemotherapy resistance. Emerging evidence show that epigenetic factor SIRT7 is involved in various aspects of cancer biology while inactive SIRT7 reverses human cancer phenotype and suppress tumor growth. In present study, we predicted SIRT7 structure by using homology modeling and performed structure-based virtual screening to develop specific SIRT7 inhibitor by docking 939319 structurally diverse compounds with structure of SIRTs proteins. Compounds with high affinity to SIRT7 but low affinity to other SIRTs proteins were chose as candidates of SIRT7 inhibitor. Our leading compounds, 2800Z and 40569Z showed strong interactions with SIRT7 protein, specifically inhibit SIRT7 deacetylation activity in vitro. Our docking results also revealed that ARG-120, TRP-126 and HIS-187 were critical sites responsible for interaction of SIRT7 to small molecules. Mutations in above sites significantly abolished interaction and inhibitory effects of compounds to SIRT7. In addition, in vivo data indicated that compounds 2800Z and 40569Z were able to induce apoptosis and increase chemosensitivity to Sorafenib in human liver cancer. Our data thus strongly suggest SIRT7 represents a druggable target in human cancer and provides valuable preclinical evidence supporting the combinatorial use of SIRT7 inhibitor with Sorafenib for human liver cancer